Assessment and treatment of self‐control with aversive events. Issue 1 (7th July 2019) - Porter, Allen; Sy, Jolene R.
Abstract : Self‐control can be defined as choosing a smaller, immediate aversive event over a larger, delayed aversive event (e.g., flossing daily instead of risking major dental problems later). Children with developmental disabilities have been found to respond impulsively when given the choice between aversive events that differ based on magnitude and difficulty. However, qualitative differences between events may also impact aversiveness. This study attempted to replicate and extend prior research by (i) empirically identifying a hierarchy of qualitatively different aversive tasks for three individuals with developmental disabilities by evaluating their average latency to escape responses when presented with each task, (ii) assessing baseline levels of self‐control (i.e., selection of immediate, low‐aversive tasks over delayed, high‐aversive tasks), and (iii) implementing an empirically validated treatment (i.e., adding a delay to both tasks). Each participant initially made impulsive choices, but self‐control increased following treatment.